Diversifying local agriculture: Agricultural diversity on smallholder farms and in local markets in Western Kenya - Keding, G.B.; Ng'endo, M. (Bioversity International, 2015)
Beyond staple foods, agriculture needs a stronger focus on nutrient-dense foods (vegetables, fruits, legumes and animal source foods), suggesting the diversification of smallholder production, such as integrated farming systems. To understand the availability of agricultural biodiversity, working with partners that included the community members themselves, a farm inventory of cultivated and wild foods was carried out on 60 farms in four different districts in Western Kenya. In addition, surveys were undertaken in 15 local markets identifying the sources of food farmers were depending on for the different food groups. While the survey took place only during one point in time, seasonal availability of foods was also considered and surveyed through focus group discussions with farmers. Results showed that food availability is highly seasonal, especially in semi-arid regions, and foods are largely sourced from the own farm with the market playing an important role in closing food and preference gaps. Stronger communication/information for and by agriculture extension workers on nutrition and the importance of dietary diversity is needed. Thereby, knowledge about different food types within one food group and their nutritional values is important. In addition, understanding how they can replace each other in order to not rely on one food plant species within one group only is key.